2020
DOI: 10.1097/md.0000000000019612
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms and serum biomarkers involved in sex differences in pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a disease associated with high mortality, but notable sex differences have been observed between males and females. For this reason, further research on the mechanisms underlying sex differences in PAH is required to better understand and treat the disease. This study mainly focused on gene expression levels to investigate potential differences in the pathogenesis and progression of PAH between the male and female sexes. Sex-specific differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Using the PubMed database [ 69 ], we collected all the DEGs (of hypertensive compared with normotensive patients) that we could find ( Table 5 ). The total number of hypertension-related human DEGs found was 7865, as cited in the rightmost column of Table 5 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the PubMed database [ 69 ], we collected all the DEGs (of hypertensive compared with normotensive patients) that we could find ( Table 5 ). The total number of hypertension-related human DEGs found was 7865, as cited in the rightmost column of Table 5 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we analyzed all the publicly available independent experimental RNA-Seq datasets—on transcriptomes from the tissues of hypertensive versus normotensive patients [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], hypertensive versus normotensive animals [ 7 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], and domestic versus wild animals [ 72 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Takahashi and coworkers [16] found increased LCN2 expression in dermal microvascular endothelial cells and speculated this may contribute to PH progression in systemic sclerosis. Li et al [22] found LCN2 to be the only gene significantly expressed in females with PH. In our study, increased expression of LCN2 was as-sociated with PH and hence we postulate this may explain the increased incidence of pulmonary vascular disease associated with CHD.…”
Section: Discussionmentioning
confidence: 99%